Sang Kristus dalam Kesusasteraan Indonesia Modern [Jesus Christ in Indonesian Modern Literature] - Abednego Tri Gumono (Diligentia: Journal of Theology and Christian Education, 2020)
Modern Indonesian literary works have various themes which are the writer's vision. One of the themes offered by the author is how humans relate to God. In the journey of modern Indonesian literature that stretches from Balai Pustaka to the present, it is a very prominent theme of God. God in Modern Indonesian literature is known as God in the general sense and God in the sense of what is known as Christianity as Jesus Christ. The aim of this research is to find a way to get Christ in Modern Indonesian Literature. The object of research is poetry and prose. These poems include Amir Amir Hamzah’s “Padamu Jua,” Chairil Anwar’s “Isa,” “Balada Penyaliban” by W.S. Rendra, Sutardji Calzoum Bachri’s “Kucing,” Djoko Damono’s “Aku Ingin,” and “Saman” by Ayu Utami. The method used in this study is a structural semiotic method that uses qualitative. The Semiotic Structural Method examines Language as a sign structure that has meaning. Qualitative recommendations are discussions that focus on the study of data containing words or sentences. It can be concluded that the works which are the object of this study have aspects of God that are both in general view and those who believe in Jesus Christ.